Dynamic Changes of Staphylococcus aureus Susceptibility to Vancomycin, Teicoplanin, and Linezolid in a Central Teaching Hospital in Shanghai, China, 2008–2018 - Jian, Ying; Lv, Huiying; Liu, Junlan; Huang, Qian; Liu, Yao; Liu, Qian; Li, Min (Frontiers in Microbiology, 2020)
Vancomycin, teicoplanin and linezolid are the major treatment options for methicillin-resistant Staphylococcus aureus (MRSA). The phenomenon of progressive increase in the value of vancomycin minimum inhibitory concentration (MIC) for S. aureus, (i.e., vancomycin MIC ‘creep’), has been reported, however it is still a controversial concept because the results of research remain inconclusive. In this study, we conducted a retrospective epidemiologic investigation for more than 10 years to elucidate the dynamic changes of the MICs of vancomycin, teicoplanin and linezolid in S. aureus in a central teaching hospital in Shanghai, China. A total of 2911 S. aureus isolates was recovered from 2008 to 2018, to which the MICs of three antimicrobials were tested by the E-test method and subsequently correlated with the characteristics of oxacillin susceptibility, clonotypes and antimicrobial consumption during the study period. The proportion of MRSA dramatically decreased from 2008 to 2018 (from 84% to 49%, p<0.001). Vancomycin MIC decline was identified both in MRSA and MSSA (both with p<0.001), and both the dominating MRSA clone ST5 and pre-dominating MRSA clone ST239 displayed vancomycin MIC decline (p<0.001, p=0.040), while teicoplanin MIC decline was only identified in MRSA (P=0.037). Linezolid MIC creep was identified in total S. aureus (p<0.001), but linezolid in MRSA as well as teicoplanin and linezolid in MSSA displayed no statistically distinct trends of MIC creep or decline. Clinical consumption of linezolid increased significantly from 2012 to 2018 (p=0.003), which correlated with vancomycin MIC decline in S. aureus (p=0.005). The results of this study clearly demonstrate the dynamic changes of the MICs of these three primary antimicrobials in S. aureus, and suggest that changes in clinical antibiotic use may affect bacterial resistance.